Construction of Defective Zinc–Cadmium–Sulfur Nanorods for Visible‐Light‐Driven Hydrogen Evolution Without the Use of Sacrificial Agents or Cocatalysts. Issue 4 (20th January 2020) - Zhang, Guoqiang; Ling, Xiang; Liu, Guoshuai; Xu, Yangsen; Xiao, Shuning; Zhang, Qitao; Yang, Xun; Qiu, Chuntian; Mi, Hongwei; Su, Chenliang
Abstract: Solar‐driven H2 evolution is an essential process for sustainable energy development. Currently, the greatest challenge is the development of efficient photocatalysts to drive this reaction, especially in pure water systems (without the use of a sacrificial agent). In this study, structural defects in Zn–Cd–S nanorod photocatalysts are found to increase charge separation efficiency significantly by sevenfold. Efficient H2 evolution (352.7 μmol h −1  g −1, 100 mg of catalyst) is achieved by using this defective Zn–Cd–S nanorod photocatalyst in the absence of sacrificial agents and precious metal cocatalysts under visible‐light irradiation. Thus, this cocatalyst‐ and sacrificial‐agent‐free, visible‐light‐responsive system shows remarkable potential as a new artificial photosynthesis route for green H2 production. Abstract : Defective is effective : A defective Zn–Cd–S photocatalyst is prepared on a large scale and used to perform water splitting with a high apparent quantum yield (5.0 % at λ =420 nm) towards H2 evolution in a system without a cocatalyst or sacrificial agent.